Unique Abnormalities in Right Ventricular Longitudinal Strain in Systemic Sclerosis Patients - Mukherjee, Monica (Circ Cardiovasc Imaging, 2016)
BACKGROUND: Cardiac involvement in systemic sclerosis (SSc) adversely affects long-term prognosis, often remaining undetectable despite close clinical examination and 2D echocardiographic monitoring. Speckle derived strain of the right ventricle (RV) was utilized to detect occult abnormalities in regional and global contractility in SSc patients. METHODS AND RESULTS: 138 SSc patients with technically adequate echocardiograms were studied, and compared with 40 age- and gender-matched healthy non-SSc controls. Standard assessment of RV chamber function included tricuspid annular plane systolic excursion (TAPSE) and fractional area change (FAC). RV longitudinal systolic speckle-derived strain (RVLSS) was assessed in the basal, mid and apical free wall. TAPSE, was not different between groups (p=0.307). While FAC was lower in SSc patients compared to controls (mean 48.9 vs. 55, p=0.002), the mean FAC was still within the normal range (>35). In contrast, RVLSS measures were significantly different between groups, both globally (-20.4 vs -17.7%, p=0.005), and regionally: decreased in the apex (-8.5 vs -17.1%, p<0.0001) and mid segments (-12.4 vs -20.9%, p<0.0001) and increased in the base (-32.2 vs -23.3%, p=0.0001)for SSc group. The regional difference in the base compared to the apex was significantly greater for SSc than controls (p<0.0001 for interaction). The differences observed in regional strain between SSc and control were unchanged after adjusting for RVSP. CONCLUSIONS: Speckle-derived strain reveals a heterogenous pattern of regional heart strain in SSc that is not detected by conventional measures of function, suggestive of occult RV myocardial disease.